Sosialisasi Dan Pendampingan Tata Kelola Keuangan UMKM Berbasis Digital Di Kelurahan Karangsari, Kecamatan Sukorejo, Kota Blitar - Aisyah Desravi Putri; Supriyono Supriyono (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
One of the problems that is often carried out by MSME actors is not recording and/or recording conventionally. Such records can cause business financial data to be lost, wet, distorted and other problems. Digital-based financial governance is a solution to the problems faced by partners. The partner of the community service activities in this journal is Ms. Anik Riyani who owns a business in Karangsari Village, Sukorejo District, Blitar City. The method used is through 3 stages, the first stage is problem identification through questionnaires and interviews. The second stage is implementation by means of socialization and digital financial management assistance through the BukuWarung application. The third stage is evaluation and maintenance which will contain criticism, suggestions and input from partners and ongoing assistance while the community service activities are still ongoing.